The Relationship between Staging and SUVmax in Non-Small Cell Lung Cancer - Kaya, H.; Balci, T.; Komek, H.; Cengiz, M. (Springer, 2015)
[Abstract Not Available]
28th Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 10-14, 2015 -- Hamburg, GERMANY